POLITICAL ECOLOGY AND TERRITORIAL PRACTICE - Bresso-, Mercedes; Raffestin, Claude; Saquet, Marcos Aurelio [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2024)
The abundance of texts already published, founded on captivating metanarratives concerning political ecology, is remarkable. However, they frequently fail to transcend the realm of discourse. Many texts lack a coherent conception of the world that aligns with their narratives. Consequently, theories, categories, and concepts are often reproduced without adequate theoretical-methodological and political scrutiny. Thus, we have chosen to contemplate the subject from a broader perspective, drawing upon our experiences in teaching, research, and university extension. Initially, we delineate fundamental aspects of the territorial dimension within a political ecology genuinely committed to the present and future of humanity. This reflection is followed by considerations of a territorial praxis that we boldly assert as decolonial and entirely consistent with our worldview. One notable outcome is the recognition of short circuits in food production, circulation, and consumption as viable alternatives, extensively demonstrated and pondered upon, for practicing socially and environmentally responsible political ecology. Another observed outcome underscores the necessity for substantial subversion within hegemonic science - characterized by its universalist and globalising tendencies- in favor of the (im)material singularities of each time-territory.
Keywords: Political ecology; Short circuits; Participatory-action-research; Popular territorial science